Necessity Entrepreneurs: Drivers and Characteristics - Chan Weng Kwai (Pusat Riset dan Inovasi Nasional, 2023)
On 11th March, 2020, World Health Organisation (WHO) declared COVID-19, a pandemic. Malaysia Government implemented ‘Movement Control Order’ or full lockdown on 18th March, 2020 causing unemployment to reach to 4.55% in 2020 and reached 5.3% in May 2020 - indicating the highest rate, for the past 20 years as reported by Department of Statistics Malaysia (DOSM). On the 1st April 2022, Malaysia transitioned to an endemic phase, leading to a gradual increase of its economic activities, especially opening up of more food and beverage services (F&B) businesses. This study examined the factors which are drivers and characteristics, which lead to necessity entrepreneurs (NE) preferably choose F&B services businesses. The two research questions are ‘What are the drivers of NE who are involved in the F&B services businesses?’ and ‘What are the entrepreneurial characteristics of NE who are involved in the F&B services businesses?’ Literature reviews were carried out on entrepreneurship, NE (Serviere’s Venture Creation Model for NE, 2010) and entrepreneurial characteristics (Ernst & Young’s Entrepreneur Model, 2011). The research design is an exploratory case study qualitative research with an in-depth semi-structured interview session, comprising of a pilot study, and a main study of 21 F&B services in Ipoh city. Thematic analysis was carried out with the ‘ATLAS.ti 23’ software. Findings suggested four novel drivers of NE, viz. family cohesion; inherited culinary skills; pursuit of culinary ambition; and unmotivated in job. Furthermore, eight novel characteristics of NE comprising perseverance; patience; money management; wellness; kinship; creativity; communication network; and self-discipline.